Release From Glomerular Overload by the Addition of Low-dose Thiazide in Patients With Angiotensin Receptor Blocker-Resistant Hypertension - Hajime Hasegawa; Yosuke Tayama; Kaori Takayanagi; Juko Asakura; Toru Nakamura; Kenji Kawashima; Taisuke Shimizu; Takatsugu Iwashita; Tomonari Ogawa; Akihiko Matsuda; Tetsuya Mitarai (Karger Publishers, 2013)
Background/Aims: This multicenter, prospective, observational study assessed the renoprotective effects of losartan/thiazide combination therapy in terms of lowering the estimated glomerular filtration rate (eGFR). Methods: Adult patients with angiotensin receptor blocker (ARB)-resistant essential hypertension (n = 104) were enrolled and switched to combination therapy with losartan (50 mg/day) and hydrochlorothiazide (12.5 mg/day). Results: eGFR values declined significantly during the first 3 months, and changes in eGFR were assessed according to tertiles of the eGFR decrease ratio at 3 months. Only the high eGFR decrease (1st tertile) group showed significantly greater decreases in baseline eGFR and albumin-to-creatinine ratio (ACR) during the first 3 months. Additionally, the assessment according to tertiles of the baseline eGFR showed a signifcant decrease in eGFR and ACR during the first 3 months in the high baseline eGFR (1st tertile) group, but not in the moderate (2nd tertile) and low baseline eGFR (3rd tertile) groups. Conclusion: The present results revealed that losartan/thiazide combination therapy attenuated glomerular overload, indicating that this therapy may provide glomerular protection in patients with an elevated GFR without causing prolonged damage to renal function.